2008
DOI: 10.1002/ijc.23597
|View full text |Cite
|
Sign up to set email alerts
|

HMG‐CoA reductase expression in breast cancer is associated with a less aggressive phenotype and influenced by anthropometric factors

Abstract: Although several studies have reported on the anti-tumoural properties exerted by 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoAR) inhibitors (statins), the in vivo expression of HMG-CoAR in human cancer has been considerably less investigated. In our study, we examined the immunohistochemical expression of HMG-CoAR in 511 incident breast cancers within the Malmö Diet and Cancer Study in order to explore its relationship to established clinicopathological and tumour biological parameters. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
66
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 29 publications
(34 reference statements)
13
66
0
1
Order By: Relevance
“…In addition, we showed that f3-hydroxy-f3-methylglutaryl CoA reductase (HMG-CoA) reductase expression, a mevalonate pathway enzyme upstream of FPPS, was low in B02 cells as compared with that observed in T47D and MCF-7 cells (12). These results agree with an earlier report (18) (12,18, and this study), these results show that IPP/ApppI production in breast cancer cells depends on cellular uptake of N-BP and on mevalonate pathway activity associated with the ER status of the cell.…”
Section: N-bps Induced Human Vg9vd2 T-cell Expansion In Vitro and In supporting
confidence: 94%
“…In addition, we showed that f3-hydroxy-f3-methylglutaryl CoA reductase (HMG-CoA) reductase expression, a mevalonate pathway enzyme upstream of FPPS, was low in B02 cells as compared with that observed in T47D and MCF-7 cells (12). These results agree with an earlier report (18) (12,18, and this study), these results show that IPP/ApppI production in breast cancer cells depends on cellular uptake of N-BP and on mevalonate pathway activity associated with the ER status of the cell.…”
Section: N-bps Induced Human Vg9vd2 T-cell Expansion In Vitro and In supporting
confidence: 94%
“…2D). These results agree with data reported by Borgquist and colleagues (32) who showed that high HMG-CoA reductase expression correlated positively with ER expression in tumor tissue from patients with breast cancer. Altogether, these results show that IPP/ApppI production in breast cancer cells depends on cellular uptake of NBP and on the activity of the mevalonate pathway.…”
Section: Zol Induces Ipp/apppi Production In Human Breast Cancer Cellsupporting
confidence: 93%
“…As our work was in progress, three tissue microarray studies reported that higher expression of HMGCR correlates with favorable breast and ovarian cancer patient prognosis (38)(39)(40). However, the antibody used in their studies is one that we showed is unable to detect human HMGCR (Fig.…”
Section: Discussionmentioning
confidence: 89%